Wolne Związki . pismo Niezależnego Samorządnego Związku Zawodowego "Solidarność", no. 20, 1981 - [EIC Jarosław Wenderlich] (NSZZ "Solidarność", 1981)
Creation and circulation: For trade-union internal use; After introduction of the Martial Law publication suspended in 1982-1987. Republished in 1988-1989. From issue no. 1=40(1990) published legally